Integrating Simalungun Culture in Indonesian Schools: A Sociocultural Analysis of Educational Socialization - Hadiani Fitri; Zuraida Adlina (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
The Simalungun culture, a vital part of the Batak ethnic identity in North Sumatra, is increasingly at risk of marginalization due to the accelerating influence of globalization and national standardization in education. Despite policy allowances for local content (muatan lokal), the incorporation of Simalungun cultural elements into formal schooling remains inconsistent and largely superficial. This study aims to investigate how educational institutions can serve as effective agents of cultural socialization to preserve and transmit Simalungun cultural identity among youth. Employing a qualitative interpretive approach, the research integrates ethnographic observation, in-depth interviews, and discourse analysis of curriculum documents across five Simalungun-majority schools. Data were analyzed using NVivo and interpreted through the lenses of Vygotsky’s sociocultural theory and Bourdieu’s concept of cultural capital. The findings reveal major structural and pedagogical barriers: most teachers lack training in Simalungun traditions, curriculum content is minimal, and student cultural awareness is declining. However, the study also identifies effective practices in schools that involve community elders and use experiential methods, demonstrating improved student engagement and cultural retention. A Cultural Transmission Score (CTS) of 0.46 confirms the limited efficacy of current efforts. The study concludes that formal education systems must move beyond ceremonial inclusion to structural integration of local culture, supported by teacher development and community-school collaboration. These insights offer a scalable framework for strengthening indigenous cultural education in minority contexts.